2002
DOI: 10.1046/j.1525-139x.2002.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Editorials: Assessment of Blood Pressure in Hemodialysis Patients

Abstract: It is self-evident that accurate measurement of blood pressure (BP) is essential for the diagnosis and treatment of hypertension. Patients on hemodialysis typically do not have their BP measured under standardized conditions, a source of error in the assessment of their BP. However, their are some unique sources of error involving interdialytic weight gain, occurrence of sleep apnea and consequent nocturnal hypertension, inability to take BP in both arms in patients who have hemodialysis angioaccess in the arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 49 publications
0
39
0
2
Order By: Relevance
“…In part, these controversies have arisen because of inadequate BP assessment techniques in hemodialysis units. The accurate measurement of arterial pressure is the essential first step in managing this cardiovascular risk factor, yet the best way to diagnose hypertension among hemodialysis patients remains unknown (7,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In part, these controversies have arisen because of inadequate BP assessment techniques in hemodialysis units. The accurate measurement of arterial pressure is the essential first step in managing this cardiovascular risk factor, yet the best way to diagnose hypertension among hemodialysis patients remains unknown (7,8).…”
mentioning
confidence: 99%
“…There are several options available for assessment of hypertension among hemodialysis patients (7). These options include techniques to obtain BP both in and out of dialysis units (9).…”
mentioning
confidence: 99%
“…Whereas many have suggested that blood pressure (BP) recordings are of little value in managing cardiovascular risk (3,4), others have argued that BP control is important (2,5,6). The accurate measurement of arterial pressure is the essential first step in managing this cardiovascular risk factor, yet the diagnosis of hypertension in hemodialysis patients continues to be a vexing problem (7,8).…”
mentioning
confidence: 99%
“…Measurements immediately at the start of haemodialysis may be subject to biases from the white coat effect on blood pressure due to the anticipatory anxiety with cannulation of the fistula or graft. 11 Those measured immediately after haemodialysis may also be confounded by the incomplete intercompartmental fluid shift.…”
mentioning
confidence: 99%